Evaluation of a patient and public involvement training programme for researchers at a large biomedical research centre in the UK - Simon Denegri; Rosamund Yu; Bec Hanley; Jaber Ahmed; Nicholas J McNally (BMJ Open, 2021)
Objectives To design, deliver and evaluate a programme of training workshops for biomedical researchers aimed at building confidence and skills in actively involving patients and the public (PPI) in research.Design A bespoke programme of training workshops in PPI aimed at researchers.Setting A large National Institute for Health Research Biomedical Research Centre in London and several partner organisations.Participants 721 scientists, clinicians and research managers attending dedicated training in PPI at a major London NHS (National Health Service)–university partnership.Interventions A programme of 72 training workshops, designed to build practical skills and confidence for researchers working with patients and the public in research, was delivered at a major research-active NHS:university partnership. An iterative approach was taken to the programme, with the content of the workshops continually reviewed and refreshed to respond to the needs of researchers. Surveys before, immediately following and 6 months after training investigated the impact on researchers’ confidence and skills in PPI work, and the kind of PPI they subsequently carried out.Results Training brought about immediate marked increases in researchers’ self-reported confidence to carry out PPI activities within their research, and in their knowledge of good practice. The evaluation indicates that workshop attendees were more likely to involve patients in their research following training. Researchers tended to involve patients and the public in a range of areas, including input to study design and patient information, in particular.Conclusions When positioned within a broader organisational strategy for PPI in research, such training has an important role to play in progressing PPI in a major research partnership. Training appeared to provide the confidence needed to carry out PPI which enabled further development of confidence and skills. Involving researchers who have attended the training in the ongoing development of the programme and bringing in patients to the training programme are key next steps.